Empowering Higher Education through a Micro-Credential Program in Power Electronics Course (Asean Journal of Engineering Education, 2023)
In line with the global and national shifts towards enhancing educational accessibility, flexibility, and quality, Malaysia has embarked on a transformative journey with the implementation of the Malaysian Education Blueprint 2015–2025 (Higher Education) and E-Learning Guidelines for Malaysian Higher Education Institutes. This strategic initiative acknowledges the pivotal role of e-learning in shaping the future of education by enabling greater access to knowledge and skills. The COVID-19 pandemic has further accelerated the growth of e-learning, emphasizing the need for innovative educational approaches. This paper presents a micro-credential program in the field of power electronics, aligned with Malaysia's commitment to advancing higher education through technology-driven solutions. The curriculum, which is tailored to meet the needs of a wide range of learners, covers all the fundamentals of power electronics and leaves participants with specific knowledge and abilities. This micro-credential program is designed to empower professionals and students, supporting their career objectives in the dynamic power electronics industry, by emphasizing accessibility, flexibility, and high-quality learning experiences.
Keywords: Micro-credentials; Power Electronics; Online Learning; Lifelong Learning; Massive Open Online Courses